Walking ability in patients with arthrogryposis multiplex congenita - Eamsobhana, Perajit (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Arthrogryposis multiplex congenita (AMC) is a multiple joint condition which affects both lower and upper extremities and thus affects ambulation. Multiple surgeries are needed to correct limb deformity in order to promote walking. The objective of this study is to identify the most critical residual deformity that diminishes the ambulatory status. MATERIALS AND METHODS: 51 patients were included in this study, 14 patients were nonambulatory. The mean age at first surgery was 4.1 years (range 2-16 years). The mean length of followup was 44.0 months (range 22-168 months). Type of procedures and number of operations, residual deformity and walking ability were recorded. Residual deformity including hip flexion contracture more than 30°, knee flexion contracture more than 30°, scoliosis, hip dysplasia or dislocation, knee extension contracture or recurvatum, active motion of hips and knees and upper limb involvement were evaluated. Statistical analysis was done to evaluate factors that were statistically significant to affect walking ability in AMC patients. RESULTS: At the latest followup, 31 patients were community ambulators, 3 patients were household ambulators, 3 patients were nonfunctional ambulatory, and 14 patients were nonambulatory. There were an average of 4.3 surgeries per patient. Statistical analysis of all factors was done and the results were significant with a P < 0.037 in knee flexion contracture >30 degrees with odds ratio of 4.58. Hip flexion contracture >30° was a trend toward significant with a P value of 0.058 and odds ratio of 4.53. Multivariate analysis showed that knee flexion contracture was significant with 4.58 (95% CI 1.01-20.6). CONCLUSION: AMC is a rare disease that causes disability, requiring multiple surgeries to correct deformities. Our study showed that residual knee flexion contracture was associated with nonambulatory status of patients with AMC.